Comparison of nurse educators’ and nursing students’ descriptions of teaching codes of ethics - Numminen, Olivia (Nursing ethics, 2011)
This study analysed teaching of nurses’ codes of ethics in basic nursing education in Finland. A total of 183 educators and 214 students responded to a structured questionnaire. The data was analysed by SPSS. Teaching of nurses’ codes was rather extensive. The nurse-patient relationship was highlighted. Educators assessed their teaching statistically significantly more extensive than what students’ perceptions were. The use of teaching and evaluation methods was conventional, but differences between the groups concerning the use of these methods were statistically significant. Students’ knowledge of and their ability to apply the codes was mediocre. Most educators and students assessed educators’ knowledge of the codes as adequate for teaching. These educators also taught the codes more extensively and these students perceived the teaching as more extensive. Otherwise educators’ and students’ socio-demographic variables had little association with the teaching. Research should focus on the organization and effectiveness of ethics education, and on educators’ competence.